Nickel-cobalt catalyst for AEM water electrolysis hydrogen production, preparation method of catalytic electrode and application of nickel-cobalt catalyst and catalytic electrode
The preparation of nickel-cobalt catalysts by hydrothermal method solves the problems of high cost of precious metal catalysts and poor binding force of non-precious metal catalysts, and realizes a low-cost and high-performance AEM electrolytic hydrogen production catalytic electrode, which is suitable for the field of AEM electrolytic hydrogen production.
Patent Information
- Application Number
- CN202510651679.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-20
- Publication Date
- 2025-09-02
AI Technical Summary
In the existing AEM electrolytic hydrogen production, precious metal catalysts are costly, and the preparation process of non-precious metal catalysts is complex and the binding force is poor, making it difficult to achieve large-scale production.
NiSO4·6H2O, (NH4)6Mo7O24·4H2O, CoCl2·6H2O and Na2S·9H2O as raw materials were used to prepare a nickel-cobalt catalyst by hydrothermal method, combined with sodium citrate as complexing agent, and control the particle size and microstructure of the product particle, and prepare (NiMoCo)xSy catalyst, and coat it on carbon cloth or nickel felt to form a catalytic electrode.
It reduces the cost of catalyst preparation, has simple process and good repeatability, excellent catalytic performance and strong binding force. It is suitable for AEM electrolysis of water hydrogen production, and has great industrial potential.
Smart Images

Figure CN120575223A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis catalysts, and in particular to a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen, a preparation method of a catalytic electrode and applications thereof. Background Art
[0002] Currently, in AEM (Anion Exchange Membrane) water electrolysis for hydrogen production, the majority of cathode hydrogen evolution reaction (HER) catalysts are precious metal-based catalysts containing platinum (Pt), such as Pt / C and PtNi. A smaller number use NiMo alloys as catalytic electrodes. Pt / C is typically prepared using an impregnation reduction method: a specific ratio of H2PtCl6 or Pt(NH3)4Cl2 solution is thoroughly mixed with carbon black treated with nitric acid for hydrophilization using ultrasonic agitation to allow the carbon black to fully absorb the Pt element. The carbon black is then heated and dried to remove the solvent, and Pt / C is then reduced in the liquid phase using NaBH4, HCHO, or ethylene glycol as a reducing agent, or in the gas phase using an H2 / N2 mixture.
[0003] The large-scale preparation process of PtNi catalyst is the same as above, which adopts the impregnation reduction method: after a proper amount of hydrophilic treated carbon black is fully mixed and impregnated with a Pt / Ni salt mixed solution, the solvent is heated to evaporate, and a reducing agent such as NaBH4 is used for liquid phase reduction or a H2 / N2 reducing mixed gas is used for gas phase reduction to obtain PtNi.
[0004] High-performance NiMo alloys are typically prepared by electrochemical deposition: appropriate amounts of nickel salt and molybdenum salt are dissolved in deionized water at a specific ratio to form an electrolyte. Additives such as sodium citrate and polyvinyl pyrrolidone are added to the electrolyte to stabilize the reaction system and control the product morphology. Electroplating is then performed using a constant current using a conductive substrate such as nickel felt or carbon cloth as an electrode. The plated sheet is then washed and dried, then calcined at high temperature in a reducing atmosphere of H2 to produce a substrate-supported NiMo alloy catalyst.
[0005] The above are all commonly used cathode catalysts and their preparation methods for AEM water electrolysis. Although Pt / C and PtNi offer excellent catalytic performance, limited by the low natural reserves and high price of Pt, they are not conducive to the long-term development of AEM water electrolysis. NiMo alloys offer excellent catalytic performance, but the electroplating process requires high equipment and space, resulting in high requirements for large-scale production, difficulty in ensuring the bonding strength between the catalyst layer and the conductive substrate, and the tendency for Pt to fall off during use, making process control complex. Summary of the Invention
[0006] Based on the technical problems existing in the background technology, the present invention proposes a nickel-cobalt catalyst for AEM electrolysis of water to produce hydrogen, a preparation method of a catalytic electrode and its application.
[0007] The present invention provides a method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen, comprising the following steps:
[0008] S1, NiSO4·6H2O, (NH4)6Mo7O 24 4H2O, CoCl2·6H2O and sodium citrate are dissolved in deionized water to obtain a first mixed solution; wherein the molar ratio of Co:Mo:Ni is 4:2:10-10:2:10; and the amount of sodium citrate is 1-2 times the total molar amount of the metal elements;
[0009] S2, dissolving Na2S·9H2O in deionized water to obtain a second mixed solution; wherein the amount of Na2S·9H2O is 1.1-2 times the total molar amount of the metal element;
[0010] S3, stirring, dissolving, and mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0011] S4, placing the hydrothermal reaction solution in a hydrothermal reactor with a set reaction temperature, and reacting at a set stirring rate for a preset reaction time; wherein the reaction temperature is 120° C.-180° C.; the stirring rate is 180 rpm-250 rpm; and the reaction time is 3 h-8 h;
[0012] S5, high-speed centrifugation to obtain powder;
[0013] S6, washing the powder with deionized water;
[0014] S7, placed in oven to dry;
[0015] S8, grinding, to obtain (NiMoCo) x S y Catalyst; wherein x is the coordination number of the metal element in the obtained catalyst crystal, and y is the coordination number of the sulfur element in the obtained catalyst crystal.
[0016] Furthermore, the NiSO4·6H2O is 134.1 g, 0.3 mol; the (NH4)6Mo7O 24 ·4H2O is 126g, 0.06mol; the CoCl2·6H2O is 47.4g-118.8g, 0.12mol-0.3mol.
[0017] Furthermore, the Na2S·9H2O is 126.8g-317g, 0.52mol-1.32mol; and the sodium citrate is 123.8g-340.6g, 0.48mol-1.32mol.
[0018] Preferably, the reaction temperature is 150° C., the reaction time is 5 h, and the stirring rate is 220 r / min.
[0019] Furthermore, the temperature of the oven is 80°C.
[0020] Furthermore, the capacity of the hydrothermal kettle is 20 L, and the hydrothermal reaction solution is 15 L.
[0021] Furthermore, the deionized water is 7.5L.
[0022] The present invention provides a nickel-cobalt catalyst, which is prepared by the preparation method of the nickel-cobalt catalyst for producing hydrogen by electrolysis of water using AEM.
[0023] The present invention provides a catalytic electrode, which is prepared from the nickel-cobalt catalyst and includes the following preparation steps:
[0024] Dispersing the catalyst powder and the binder in a solvent according to a set ratio to obtain a slurry;
[0025] The slurry is coated on carbon cloth and dried to obtain a catalytic electrode.
[0026] The present invention also provides an application of a nickel-cobalt catalyst, wherein the nickel-cobalt catalyst is applied to hydrogen production by electrolysis of water by AEM.
[0027] The present invention has the following beneficial effects:
[0028] This application uses transition metals as raw materials, which can significantly reduce the preparation cost of the catalyst compared to precious metals. The catalyst is prepared using a hydrothermal method, which has low equipment requirements, good process repeatability, and stable product properties. The prepared powder catalyst can be prepared into a slurry and coated on a conductive substrate such as carbon cloth or nickel felt to form a catalytic electrode. The prepared catalyst electrode has high electrochemical performance, strong binding force, and is not easy to fall off. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a process flow chart of a method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen proposed by the present invention;
[0030] Figure 2 For the present invention (NiMoCo) x S y Comparison of electrochemical performance of catalyst, Pt / C and PtNi catalytic electrodes;
[0031] Figure 3 This is a finished product diagram of a catalyst obtained by the preparation method of a nickel-cobalt catalyst for AEM electrolysis of water to produce hydrogen according to the present invention. DETAILED DESCRIPTION
[0032] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention pertains. The terms used in this specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0034] Refer to the attached Figure 1 A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen, comprising the following steps:
[0035] S1, NiSO4·6H2O, (NH4)6Mo7O 24 4H2O, CoCl2·6H2O and sodium citrate are dissolved in deionized water to obtain a first mixed solution; wherein the molar ratio of Co:Mo:Ni is 4:2:10-10:2:10; and the amount of sodium citrate is 1-2 times the total molar amount of the metal elements;
[0036] S2, dissolving Na2S·9H2O in deionized water to obtain a second mixed solution; wherein the amount of Na2S·9H2O is 1.1-2 times the total molar amount of the metal element;
[0037] S3, stirring, dissolving, and mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0038] S4, placing the hydrothermal reaction solution in a hydrothermal reactor at a set reaction temperature, and reacting at a set stirring rate for a preset reaction time; wherein the reaction temperature is 120°C-180°C; the stirring rate is 180r / min-250r / min; and the reaction time is 3h-8h;
[0039] S5, high-speed centrifugation to obtain powder;
[0040] S6, washing the powder with deionized water;
[0041] S7, placed in oven to dry;
[0042] S8, grinding, to obtain (NiMoCo) x S yCatalyst; wherein x is the coordination number of the metal element in the obtained catalyst crystal, and y is the coordination number of the sulfur element in the obtained catalyst crystal.
[0043] In the above steps, (NH4)6Mo7O 24 ·4H2O is ammonium molybdate tetrahydrate, and NiSO4·6H2O and (NH4)6Mo7O 24 The amount of 4H2O used is constant.
[0044] First, NiSO4·6H2O, (NH4)6Mo7O 24 ·4H2O, CoCl2·6H2O, and sodium citrate were dissolved in 7.5L of deionized water to obtain a first mixed solution; wherein the molar ratio of Co:Mo:Ni was 4:2:10-10:2:10. The composition of the catalyst was regulated by adjusting the amount of CoCl2·6H2O. The amount of CoCl2·6H2O was 47.4g-118.8g, 0.12mol-0.3mol; the amount of NiSO4·6H2O was 134.1g, 0.3mol; and the amount of (NH4)6Mo7O was 0. 24 4H2O is 126g, 0.06mol; the amount of sodium citrate used ranges from 123.8g to 340.6g, 0.48mol to 1.32mol.
[0045] Na2S·9H2O (126.8-317 g, 0.52-1.32 mol) was added to 7.5 L of deionized water, yielding a second mixed solution. The first and second mixed solutions were then stirred and dissolved at high speed to thoroughly mix, yielding 15 L of a hydrothermal reaction solution.
[0046] The hydrothermal reaction solution is then placed in a hydrothermal kettle at a set reaction temperature and reacted at a set stirring rate for a preset reaction time. In this application, the hydrothermal kettle is used as the reactor, and the hydrothermal reaction temperature is a key parameter in this catalyst preparation process, which can directly determine the occurrence of the reaction and the various properties of the product. If the temperature is too low, the reaction is unlikely to occur or the rate is slow; if the temperature is too high, side reactions will occur and impurities will be introduced. The hydrothermal reaction temperature range of this application is set between 120°C and 180°C, preferably at 150°C. The hydrothermal reaction time directly determines the degree of completion of the reaction. If the reaction time is too short, the reaction will not be complete; if the reaction time is too long, the product particles will tend to grow excessively, resulting in oversized catalyst particles. The hydrothermal reaction time of this application is set between 3h and 8h, preferably 5h. The stirring rate affects the hydrothermal reaction process, ensuring that the reaction occurs uniformly in the solution, increasing the collision probability of the reactant molecules, and increasing the reaction rate. It also provides shear force to break up larger particles into fine particles, which can directly affect the particle size distribution of the catalyst particles. The stirring rate of the present application is set at 180 r / min-250 r / min, preferably, set at 220 r / min. Further, the capacity of the hydrothermal kettle is 20L.
[0047] After the hydrothermal reaction is completed, the solid-liquid separation is carried out by high-speed centrifugation to obtain a dark black powder. The powder is then washed with deionized water and dried in an oven at 80°C. Finally, it is ground after drying to obtain the following: Figure 3 Shown (NiMoCo) x S y Transition metal sulfide catalysts. Here, x represents the total molar amount of the three metal elements nickel (Ni), molybdenum (Mo), and cobalt (Co). In experiments, the molar ratio of Co:Mo:Ni varies between 4:2:10 and 10:2:10. x is the coordination number of the metal elements in the resulting catalyst crystals. y represents the coordination number of sulfur (S). In experiments, the amount of sulfur used is 1.1-2 times the total molar amount of the metal elements. y varies with the total molar amount of the metal elements.
[0048] The present invention uses NiSO4·6H2O, (NH4)6Mo7O 24 ·4H2O, CoCl2·6H2O, Na2S·9H2O, sodium citrate as raw materials, and carried out by hydrothermal method (NiMoCo) x S y Catalyst preparation: In terms of material ratio and solution concentration, Ni and Co are the main components, with Mo as a minor dopant. Na2S·9H2O is added as a sulfiding agent in excess relative to the metal elements. Sodium citrate is used as a complexing agent to control the particle size and microstructure of the product and is added in multiples of the total molar amount of the metal elements.
[0049] This application uses transition metals as raw materials, which can significantly reduce the preparation cost of the catalyst compared to precious metals. The catalyst is prepared using a hydrothermal method, which has low equipment requirements, good process repeatability, and stable product properties. The prepared powder catalyst can be prepared into a slurry and coated on a conductive substrate such as carbon cloth or nickel felt to form a catalytic electrode. The prepared catalyst electrode has high electrochemical performance, strong bonding force, and is not easy to fall off.
[0050] In one embodiment, the preparation is performed using the preferred conditions as an example.
[0051] Specifically, the ingredients are prepared with a molar ratio of Co:Mo:Ni of 6:2:10, namely 71.3g CoCl2·6H2O, 134.1g NiSO4·6H2O and 126g (NH4)6Mo7O 24 4H2O was dissolved in 7.5 L of deionized water, and sodium citrate was added at a molar ratio of 1.5 times that of the metal element, that is, 197.4 g of sodium citrate and the metal salt were mixed and dissolved in 7.5 L of deionized water to obtain a first mixed solution.
[0052] Na2S·9H2O was added at 1.8 times the total molar amount of the metal elements, that is, 220.5 g of Na2S·9H2O was dissolved in 7.5 L of deionized water to obtain a second mixed solution.
[0053] After complete dissolution, the first and second mixed solutions were thoroughly mixed to obtain a hydrothermal reaction solution. This solution was then poured into a hydrothermal kettle, which was set to 150°C, with a stirring rate of 220 rpm and a reaction time of 5 hours. After the reaction was complete, the solution was centrifuged, washed, dried, and finally ground to obtain a catalyst powder.
[0054] The invention provides a nickel-cobalt catalyst, which is prepared by a method for preparing a nickel-cobalt catalyst for producing hydrogen by electrolysis of water using AEM.
[0055] The present invention provides a catalytic electrode prepared from a nickel-cobalt catalyst, comprising the following preparation steps:
[0056] Dispersing the catalyst powder and the binder in a solvent according to a set ratio to obtain a slurry;
[0057] The slurry is coated on carbon cloth and dried to obtain a catalytic electrode.
[0058] In one embodiment, the catalyst powder and a binder are dispersed in a solvent at a predetermined ratio to form a slurry. The binder may be polytetrafluoroethylene or polyvinylidene fluoride, and the solvent may be deionized water or N-methylpyrrolidone. The slurry is then coated on a carbon cloth and dried to form a catalytic electrode.
[0059] For comparison, Pt / C and PtNi catalytic electrodes were prepared using the same method, and the loading of the three catalytic electrodes was adjusted to be the same, all at 0.8 mg cm -2 Then, the three catalytic electrodes were used as cathodes, nickel-iron layered hydroxide (NiFe-LDH) was used as anode, and the same anion exchange membrane was assembled into a small AEM electrolyzer. The electrochemical performance tests were carried out respectively. The test results are as follows: Figure 2 shown.
[0060] Depend on Figure 2 It can be seen that under the same test conditions, (NiMoCo) x S y Compared with Pt / C and PtNi, it has better performance advantages. At a voltage of 2V, (NiMoCo) x S y Can achieve 1.45Acm -2 The current density is higher than Pt / C1.02Acm -2 , higher than PtNi1.20Acm -2 . It can be seen that the catalyst prepared in this application can not only avoid the use of precious metals and greatly reduce costs, but also has performance superior to precious metal catalysts. As a catalyst material, it has great potential in the field of AEM water electrolysis hydrogen production. In terms of preparation technology, this application adopts a hydrothermal method for preparation, which is not only simple to operate, has good process repeatability, and stable product properties, but also can be mass-produced according to the model of the hydrothermal kettle, with low equipment and site requirements, and can be suitable for industrial development.
[0061] The present invention also provides an application of a nickel-cobalt catalyst, wherein the nickel-cobalt catalyst is applied to hydrogen production by electrolysis of water using an AEM.
[0062] Refer to the attached Figure 1 , is a method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen in one embodiment of the present invention, wherein,
[0063] Example 1
[0064] A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen is prepared according to the following steps:
[0065] S1, 134.1g, 0.3mol of NiSO4·6H2O, 126g, 0.06mol of (NH4)6Mo7O 24 ·4H2O, 118.8 g (0.3 mol) of CoCl2·6H2O and 340.6 g (1.32 mol) of sodium citrate were dissolved in 7.5 L of deionized water to obtain a first mixed solution;
[0066] S2, dissolving 317 g and 1.32 mol of Na2S·9H2O in 7.5 L of deionized water to obtain a second mixed solution;
[0067] S3, after the dissolution is completed, mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0068] S4, placing the hydrothermal reaction solution in a hydrothermal reactor at 100° C. and reacting at a stirring rate of 200 r / min for 4 h;
[0069] S5, centrifugation to obtain powder;
[0070] S6, washing the powder with deionized water;
[0071] S7, placed in oven to dry;
[0072] S8, grinding, to obtain (NiMoCo) x S y catalyst.
[0073] Specifically, after the hydrothermal reaction was completed, the liquid phase was obviously yellow-green. After centrifugal drying, 72 g of catalyst powder was obtained. The yield was low, and the catalytic electrode prepared could only reach 0.5 A cm at a voltage of 2 V. -2 current density.
[0074] Example 2
[0075] A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen is prepared according to the following steps:
[0076] S1, 134.1g, 0.3mol of NiSO4·6H2O, 126g, 0.06mol of (NH4)6Mo7O 24 ·4H2O, 118.8 g (0.3 mol) of CoCl2·6H2O and 340.6 g (1.32 mol) of sodium citrate were dissolved in 7.5 L of deionized water to obtain a first mixed solution;
[0077] S2, dissolving 317 g and 1.32 mol of Na2S·9H2O in 7.5 L of deionized water to obtain a second mixed solution;
[0078] S3, after the dissolution is completed, mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0079] S4, placing the hydrothermal reaction solution in a hydrothermal autoclave at 150° C. and reacting at a stirring rate of 200 r / min for 4 h;
[0080] S5, centrifugation to obtain powder;
[0081] S6, washing the powder with deionized water;
[0082] S7, placed in oven to dry;
[0083] S8, grinding, to obtain (NiMoCo) x S y catalyst.
[0084] Same as Example 1, except that, in the preparation of (NiMoCo) x S y In the catalyst step, the reaction temperature of the hydrothermal reactor was changed to 150°C. After the reaction was completed, the liquid phase was clear and transparent without obvious color, and the obtained catalyst powder was 108g. The catalytic electrode can reach 0.8Acm at 2V. -2 It can be seen that as the temperature rises, the reaction becomes more complete and the catalyst performance is improved.
[0085] Example 3
[0086] A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen is prepared according to the following steps:
[0087] S1, 134.1g, 0.3mol of NiSO4·6H2O, 126g, 0.06mol of (NH4)6Mo7O 24 ·4H2O, 118.8 g (0.3 mol) of CoCl2·6H2O and 340.6 g (1.32 mol) of sodium citrate were dissolved in 7.5 L of deionized water to obtain a first mixed solution;
[0088] S2, dissolving 317 g and 1.32 mol of Na2S·9H2O in 7.5 L of deionized water to obtain a second mixed solution;
[0089] S3, after the dissolution is completed, mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0090] S4, placing the hydrothermal reaction solution in a hydrothermal reactor at 200°C and reacting at a stirring rate of 200 r / min for 4 h;
[0091] S5, centrifugation to obtain powder;
[0092] S6, washing the powder with deionized water;
[0093] S7, placed in oven to dry;
[0094] S8, grinding, to obtain (NiMoCo) x S y catalyst.
[0095] Same as Example 1, except that, in the preparation of (NiMoCo) x S y During the catalyst step, the reaction temperature was further raised to 200°C. After the reaction was completed, the catalyst produced showed signs of agglomeration. This indicates that excessively high temperatures can lead to excessive crystal growth and agglomeration between particles.
[0096] Example 4
[0097] A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen is prepared according to the following steps:
[0098] S1, 134.1g, 0.3mol of NiSO4·6H2O, 126g, 0.06mol of (NH4)6Mo7O 24 ·4H2O, 89.4 g (0.2 mol) of CoCl2·6H2O and 340.6 g (1.32 mol) of sodium citrate were dissolved in 7.5 L of deionized water to obtain a first mixed solution;
[0099] S2, dissolving 317 g and 1.32 mol of Na2S·9H2O in 7.5 L of deionized water to obtain a second mixed solution;
[0100] S3, after the dissolution is completed, mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0101] S4, placing the hydrothermal reaction solution in a hydrothermal autoclave at 150° C. and reacting at a stirring rate of 200 r / min for 4 h;
[0102] S5, centrifugation to obtain powder;
[0103] S6, washing the powder with deionized water;
[0104] S7, placed in oven to dry;
[0105] S8, grinding, to obtain (NiMoCo) x S y catalyst.
[0106] Same as Example 2, except that, in the preparation of (NiMoCo) x S y In the catalyst step, the amount of CoCl2·6H2O was reduced from 134.1g, 0.3mol to 89.4g, 0.2mol. The performance of the catalytic electrode obtained was further improved compared with Example 2, and 1.2Acm was achieved at a voltage of 2V. -2 current density.
[0107] Example 5
[0108] A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen is prepared according to the following steps:
[0109] S1, 134.1g, 0.3mol of NiSO4·6H2O, 126g, 0.06mol of (NH4)6Mo7O 24 ·4H2O, 44.7 g (0.1 mol) of CoCl2·6H2O and 340.6 g (1.32 mol) of sodium citrate were dissolved in 7.5 L of deionized water to obtain a first mixed solution;
[0110] S2, dissolving 317 g and 1.32 mol of Na2S·9H2O in 7.5 L of deionized water to obtain a second mixed solution;
[0111] S3, after the dissolution is completed, mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution;
[0112] S4, placing the hydrothermal reaction solution in a hydrothermal reactor at 200°C and reacting at a stirring rate of 200 r / min for 4 h;
[0113] S5, centrifugation to obtain powder;
[0114] S6, washing the powder with deionized water;
[0115] S7, placed in oven to dry;
[0116] S8, grinding, to obtain (NiMoCo) x S y catalyst.
[0117] Same as Example 3, except that, in the preparation of (NiMoCo) x S y In the catalyst step, the amount of CoCl2·6H2O was further reduced from 89.4 g, 0.2 mol to 44.7 g, 0.1 mol. The performance of the catalytic electrode obtained was significantly reduced compared with that of Example 3, and only 0.6 Acm was achieved at a voltage of 2 V. -2 It can be seen that the optimal molar ratio of CoCl2·6H2O to NiSO4·6H2O is 2:3 in Example 4.
[0118] In summary, compared to precious metals, the catalysts prepared using transition metals as raw materials in this application can significantly reduce catalyst preparation costs. Furthermore, the hydrothermal method employed to prepare the catalysts has lower equipment requirements, better process reproducibility, and stable product properties with high catalytic performance.
[0119] On the other hand, the electrode made from the catalyst of the present application has high electrochemical performance, strong binding force and is not easy to fall off.
[0120] The above are only preferred specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with this technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen, characterized in that: The following steps are involved: S1, NiSO4·6H2O, (NH4)6Mo7O 24 4H2O, CoCl2·6H2O and sodium citrate are dissolved in deionized water to obtain a first mixed solution; wherein the molar ratio of Co:Mo:Ni is 4:2:10-10:2:10; and the amount of sodium citrate is 1-2 times the total molar amount of the metal elements; S2, dissolving Na2S·9H2O in deionized water to obtain a second mixed solution; wherein the amount of Na2S·9H2O is 1.1-2 times the total molar amount of the metal element; S3, stirring, dissolving, and mixing the first mixed solution and the second mixed solution to obtain a hydrothermal reaction solution; S4, placing the hydrothermal reaction solution in a hydrothermal reactor with a set reaction temperature, and reacting at a set stirring rate for a preset reaction time; wherein the reaction temperature is 120° C.-180° C.; the stirring rate is 180 rpm-250 rpm; and the reaction time is 3 h-8 h; S5, high-speed centrifugation to obtain powder; S6, washing the powder with deionized water; S7, placed in oven to dry; S8, grinding, to obtain (NiMoCo) x S y Catalyst; wherein x is the coordination number of the metal element in the obtained catalyst crystal, and y is the coordination number of the sulfur element in the obtained catalyst crystal.
2. The method for preparing the nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen according to claim 1, characterized in that: The NiSO4·6H2O is 134.1 g, 0.3 mol; the (NH4)6Mo7O 24 ·4H2O is 126g, 0.06mol; the CoCl2·6H2O is 47.4g-118.8g, 0.12mol-0.3mol.
3. The method for preparing the nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen according to claim 1, characterized in that: The Na2S·9H2O contains 126.8g-317g, 0.52mol-1.32mol; and the sodium citrate contains 123.8g-340.6g, 0.48mol-1.32mol.
4. The method for preparing the nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen according to claim 1, characterized in that: The reaction temperature is 150° C., the reaction time is 5 h, and the stirring rate is 220 r / min.
5. The method for preparing the nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen according to claim 1, characterized in that: The temperature of the oven is 80°C.
6. The method for preparing the nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen according to claim 1, characterized in that: The capacity of the hydrothermal kettle is 20 L, and the volume of the hydrothermal reaction solution is 15 L.
7. The method for preparing the nickel-cobalt catalyst for AEM water electrolysis to produce hydrogen according to claim 1, characterized in that: The amount of deionized water is 7.5 L.
8. A nickel-cobalt catalyst, characterized in that The nickel-cobalt catalyst is prepared according to the preparation method of the AEM water electrolysis hydrogen production method according to any one of claims 1 to 7.
9. A catalytic electrode, characterized in that: The method is prepared from the nickel-cobalt catalyst according to claim 8, comprising the following preparation steps: Dispersing the catalyst powder and the binder in a solvent according to a set ratio to obtain a slurry; The slurry is coated on carbon cloth and dried to obtain a catalytic electrode.
10. An application of a nickel-cobalt catalyst, characterized in that: The nickel-cobalt catalyst described in claim 8 is used in AEM water electrolysis to produce hydrogen.